2016
DOI: 10.1038/cmi.2016.24
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes mediate hepatitis B virus (HBV) transmission and NK-cell dysfunction

Abstract: Evidence suggests that exosomes can transfer genetic material between cells. However, their roles in hepatitis B virus (HBV) infection remain unclear. Here, we report that exosomes present in the sera of chronic hepatitis B (CHB) patients contained both HBV nucleic acids and HBV proteins, and transferred HBV to hepatocytes in an active manner. Notably, HBV nucleic acids were detected in natural killer (NK) cells from both CHB patients and healthy donors after exposure to HBV-positive exosomes. Through real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
180
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(185 citation statements)
references
References 35 publications
5
180
0
Order By: Relevance
“…Indeed, the Cys residues within the S domain form several disulfide bonds that confer stability to the virions and might also be essential for the virion uptake and productive infection [34]. Although we did not examine the infectious ability of the isolates with sC69*, infection of new hepatocytes through alternative secretion of the isolates, as evidenced via exosomes in our study, is expected even if the incomplete structure of envelop proteins does not support the infectivity [15]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the Cys residues within the S domain form several disulfide bonds that confer stability to the virions and might also be essential for the virion uptake and productive infection [34]. Although we did not examine the infectious ability of the isolates with sC69*, infection of new hepatocytes through alternative secretion of the isolates, as evidenced via exosomes in our study, is expected even if the incomplete structure of envelop proteins does not support the infectivity [15]. …”
Section: Discussionmentioning
confidence: 99%
“…HBV progeny DNA was extracted subsequently through alcohol precipitation. To isolate HBV DNA from secreted particles, three different approaches were applied: (a) polyethylene glycol precipitation (PEG, Sigma, St. Louis, MO, USA), followed by capsid digestion and alcohol precipitation of DNA; (b) immune precipitation of released particles by using preS1 (Santa Cruz Biotechnology, USA) and core (Thermo Fisher, USA) antibodies and isolation of the DNA (QIAamp DNA mini kit, Qiagen, USA); (c) ultra-centrifugation of the supernatants (110,000x g, 70 min) [15], evaluation of the concentration of pelleted particles using the LM10 nanoparticle characterization system in real-time (NanoSight, Malvern Instruments) equipped with a blue laser (405 nm) followed by isolation of exosomes from precipitated particles by using an Exosome-Human CD63 isolation/detection reagent (Thermo Fisher) and extraction of DNA (QIAamp DNA mini kit). A 5 μl aliquot of HBV DNA isolated from immunoprecipitated particles (using preS1 and core antibodies) and exosomes was subjected per reaction well to qPCR analysis, using the iTaq Universal SYBR Green One-Step qPCR kit (BioRad, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%
“…76 Moreover, exosomes isolated from sera of chronic hepatitis B patients contain HBV viral components and can induce active infection in naive human hepatocytes. 77 Recently, Yang et al 77 found that exosomes shuttle HBV viral components into NK cells, leading to NK cell dysfunction through the downregulation of retinoic acid inducible gene I (RIGI) and inactivation of nuclear factor κB (NF-κB) and p38 mitogen-activated protein kinase pathways.…”
Section: Evs In Liver Diseasesmentioning
confidence: 99%
“…This may be used as a marker for identifying potential reactivation candidates, which needs to be validated and further longitudinal studies should be performed. The EVs carrying HBV transmits infection are already described previously by Yang et al in hepatoma cell lines. The novelty of our study is that it highlights the detection of HBV DNA in EVs when it was undetectable in plasma of same sample.…”
Section: Discussionmentioning
confidence: 99%